The effects of job displacement on the onset and progression of diabetes - Annette Bergemann; Erik Grönqvist; Soffia Gudbjörnsdottir (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Are there negative health effects from losing the job? We analyze the causal effect of job displacement on diabetes incidence and prevalence. Type 2 diabetes is an illness that is directly affected by lifestyle factors and psychosocial stress, and with severe side-effects deteriorating the quality of life. We use rich Swedish register data that allows us to identify workers displaced through plant downsizing between 2002 and 2004, matched to detailed information on diabetes status from the Swedish National Diabetes Register. As those displaced at large layoffs may still be a selective group with respect to health we match them to comparable workers not being displaced. On average we do not find signs for a significant increase in the diabetes onset in case an individual is mass-laid off. However, we find substantial effect heterogeneity when distinguishing between different socio-economic characteristics which additionally differ between men and women. For example, the probability of the onset of diabetes increases due to being mass laid off in case men do not have a partner. In addition there are signs that women in case of having a partner and a child below 18 also suffer in terms of diabetes incidence in case they are mass-laid off
Keywords: I18; J64; C14; J65; 330; unemployment; health; matching